1990
DOI: 10.1001/archderm.1990.01670320104020
|View full text |Cite
|
Sign up to set email alerts
|

Interferon

Abstract: and Lindenmann1 has led to the establishment of a new field of research involving virology, immunology, tumor destruction, cell biology, and molecular genetics, as well as other disciplines. The bearers of interference (interferons) constitute a class of glycoproteins exhibiting antitumor, antiviral, and immu-See also p 1029. nologic properties. Three types of interferons are currently recognized: interferon alfa (alpha leukocyte interferon), interferon beta (fibroblast interferon), and interferon gamma (immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…At higher doses, depression can be observed. Transiently elevated liver enzymes that normalize within 2 to 5 days after therapy have also been observed at higher doses 14 . In addition, IFNα‐2b shows a dose‐related bone marrow suppression, which is reversible with discontinuation 27…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…At higher doses, depression can be observed. Transiently elevated liver enzymes that normalize within 2 to 5 days after therapy have also been observed at higher doses 14 . In addition, IFNα‐2b shows a dose‐related bone marrow suppression, which is reversible with discontinuation 27…”
Section: Discussionmentioning
confidence: 98%
“…Other authors have observed that some lesions with partial regression at 8 weeks after treatment progressed to achieve a histologic cure (without further treatment) at 16 weeks 12 . Many authors have noted that when a lesion appears to be clinically resolved, there is histologic resolution of the tumor as well 2,13–15 . It appears that a 16‐week posttreatment period is required for adequate assessment of IFNα‐2b efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Interferons inhibit cellular growth and modulate cellular function; therefore, they exhibit antineoplastic action (1). Many studies have shown that interferons are effective treatment for BCC; IFN-a appears to have much more effect than does IFN beta or gamma (2). Their mechanism of action is unknown.…”
Section: Introductionmentioning
confidence: 99%